PENGARUH UKURAN PERUSAHAAN, TIPE INDUSTRI, PROFITABILITAS, LEVERAGE, DAN KINERJA LINKGUNGAN TERHADAP ENVIRONMENTAL DISCLOSURE (Studi Empiris Pada Perusahaan yang Terdaftar di BEI dan Menjadi Peserta PROPER Tahun 2011-2013) - Dicko Eka Bimantara Nugraha; Agung Juliarto (Diponegoro Journal of Accounting, 2015)
The objective of this research is to analyze the influence of firm size, industry type, profitability, leverage, and enviromental performance on the level of Environmental Disclosure. Measurement of  Environmental Disclosure utilizes scorecard based on Global Reporting Initiative (GRI). There are 45 items to detect  Environmental Disclosure. This research refers to research conducted by Van De Burgwal and Vieira (2014) with some modification. Population of this research were non financial companies that listed in Indonesian Stock Exchange (IDX) during 2011-2013. Data were collected by using purposive sampling method with criteria company participanting in PROPER. A total data of 105 observations were analyzed. Multiple linear regression analysis was used as a main analysis tool. The results of this research show that firm size, industry type, and environmental performance significantly influence the level of Environmental Disclosure. Whereas, profitability and leverage have no significant effects on the level of Environmental Disclosure.